Epidemiology of Helicobacter pylori, gastric precancerous lesions and gastric cancer: a multicenter, population-based cross-sectional study in Nanjing - Chunyan Niu; Yongqiang Song; Yue Chen; Yongqiang Shi; Hui Wang; Xinguo Wu; Xiaoping Wang; Xiangyang Zhao; Yongdan Bu; Jijin Li; Tao Tao; Jinhua Wu; et al. (BMC Infectious Diseases)
Abstract Background Nanjing City has a high-incidence gastric cancer (GC), but the epidemiology of gastric precancerous lesions (GPLs) remains poorly understood. This study aimed to investigate the epidemiological characteristics of Helicobacter pylori (H. pylori) infection, GPLs, and GCs in patients undergoing endoscopic examination in Lishui District, Nanjing. Methods This retrospective, population-based, cross-sectional study was conducted collaboratively by the Nanjing Lishui People’s Hospital and six medical community units within the county between July 2022 and June 2023. Data on biopsies and 13C urea breath tests (13C-UBT) were collected. Results A total of 15,668 individuals were included, among whom 259 had GPL (1.65%) and 218 had GC (1.39%). The H. pylori infection rate in total patients was 5014 (32.00%) (males: 2684 (34.06%); females: 2335 (29.92%)). The H. pylori infection rate is 31.45% in benign gastric lesions, 44.40% in GPLs, and 55.50% in GC, respectively. The multivariable logistic regression analysis showed that male (OR = 3.156, 95% CI: 2.865–3.376, P < 0.001), age (OR = 1.785, 95% CI: 1.703–1.876, P < 0.001), fresh vegetable, fruit, and white meat intake frequently (OR = 0.865, 95% CI: 0.506–2.061, P = 0.029), high-salt diet and high-fat diet intake frequently (OR = 1.906, 95% CI: 1.101–2.932, P = 0.014), rural residence (OR = 2.682, 95% CI: 1.010–4.754, P = 0.040), H. pylori infection (OR = 2.022, 95% CI: 1.155–2.865, P < 0.001) and atrophic gastritis and/or intestinal metaplasia (OR = 4.875, 95% CI: 2.229–10.663, P < 0.001) were associated with GPLs. Male (OR = 2.021, 95% CI: 1.080–3.780, P = 2.028), age (OR = 1.201, 95% CI: 1.174–1.238, P < 0.001), digestive symptoms (OR = 2.256, 95% CI: 1.548–3.289, P < 0.001), bachelor degree below (OR = 4.792, 95% CI: 3.439–6.837, P < 0.001), farmer (OR = 1.039, 95% CI: 1.026–1.159, P < 0.001), fresh vegetable, fruit, and white meat intake (OR = 0.231, 95% CI: 0.141–0.379, P < 0.001), fried/barbecue/pickled food intake (OR = 6.781, 95% CI: 3.783–12.153, P < 0.001), high-salt diet and high-fat diet intake (OR = 4.374, 95% CI: 2.363–8.097, P < 0.001), rural residence (OR = 1.230, 95% CI: 1.121–1.437, P < 0.001), H. pylori infection (OR = 3.248, 95% CI: 2.357–4.477, P < 0.001) and atrophic gastritis and/or intestinal metaplasia (OR = 4.875, 95% CI: 2.636–9.016, P < 0.001) were associated with GCs. Conclusions These findings underscore the importance of implementing targeted prevention strategies and early detection programs in high-risk populations to mitigate the burden of GPLs and GCs in Nanjing.